PENINGKATAN KETERAMPILAN MOTORIK HALUS MELALUI TEKNIK MOZAIK PADA ANAK DOWN SYNDROME DI KAMPUNG BABAKAN SAWAH - Rahayu Dwi Utami; Sima Mulyadi; Rosarina Giyartini Giyartini (PIWURUK: Jurnal Sekolah Dasar, 2021)
Improvement of fine motor skills through mosaic technique in one of the Down Syndrome children in Babakan Sawah village. This research is based on the observations and experiences of researchers that fine motor skills in one of the Down Syndrome children are still low. The limitations of the media at home, as well ase the lack of stimulus provided by parents in improving fine motor skill is less than optimal. This research is uses single case experimental method with a one child, who is seven years old, famale, as a participant involved in this research. The teachnique of collecting data is observation sheets, and documentation, while for data analysis technique using descriptive statistics. The conclusion of this research is using mosaiq technique for improvement of fine motor skills in the Down Syndrome children in Babakan Sawah village. The ability of the child’s fine motor skills before being given the intervention has not yet developed (BB), in intervention 1 begins to develop (MB), and after being given th intervention it develope as expected (BSH). From this description, it can be concluded that the application of the mosaic technique can improve fine motor skills of Down syndrome in Babakan Sawah village. Based on the conclusions, tp parents who have the Down Syndrome children, it is suggested that parents who have children with special need should be able to provide stimulus to children in improving soft motor skills